Analisis Pengaruh Pertumbuhan Ekonomi, Investasi Dan Tingkat Upah Terhadap Kesempatan Kerja Kabupaten/Kota di Provinsi Jambi - Ari Susanto; Junaidi Junaidi; Hardiani Hardiani (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
The research entitled “Analyzing The Affect of the Economic Growth, the Investment and the Wage Towards the Employment of regency/city in Jambi Province”. The purposes of this research were : (1) to analyze the economic growth, the Investments, the wage and the employment regency/city in Jambi province, and (2) to analyze the affect the economic growth, the investment and the wage towards employment regency/city in Jambi Province. With independent variable the economic growth, the Investment and the wage for regency/city while the dependent variable is employment regency/city in Jambi Province. This researcher used panel data regression. The F test indicated that simultaneously the variables of the economic growth, the investments and wage significantly affected employment regency/city in Jambi Province. while t test revealed that partially economic growth and investment affected employment regency/city in Jambi Province positively and significantly, meanwhile the wage insignificant to the employment at the regency/city in Jambi Province.